Protocol for testing global neuronal workspace and integrated information theories of consciousness in non-human primates and mice - Matilda Gibbons; Ethan G. McBride; Raghuram Holenarasipura Venkatasubbaiah; Majid Khalili-Ardali; Jacqulyn R. Kuyat; Samuel Gale; Vayle LaFehr; Nathan W. Vogler; Mohammadali Kheirkhah Ravandi; Ming-Jiun Tsai; Corbett Bennett; Arjun Sridhar; et al. (PLoS ONE, 2026)
Identifying the neural correlates of consciousness (NCC) is widely regarded as imperative to our understanding of consciousness. Although several scientific theories of consciousness make predictions about the NCC, they often differ in their level of detail, making direct comparison through experimental findings difficult. Here, we report an adversarial collaboration protocol in which unbiased experimentalists will test predictions formed by theory proponents of Global Neuronal Workspace Theory (GNWT) and Integrated Information Theory (IIT), concerning the location, timing and functional connectivity of the NCC. To enable cross-species comparisons, non-human primates (NHPs) and mice will view/listen to supra-threshold visual/auditory stimuli for variable durations in a go-nogo task that controls for report confounds, while we record with Neuropixels electrodes neuronal responses from visual, auditory, posterior parietal and/or prefrontal cortical areas. To causally test predictions about the timing and location, we will manipulate activity in prefrontal cortical regions using electrical stimulation in NHPs or optogenetic silencing in mice. This Study Protocol details the experimental design, analyses, divergent predictions, and the anticipated outcomes, along with their interpretation.